2019
DOI: 10.1111/febs.14940
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pseudomonas aeruginosa biofilm formation and expression of virulence genes by selective epimerization in the peptide Esculentin‐1a(1‐21)NH2

Abstract: Pseudomonas aeruginosa is a pathogenic bacterium known to cause serious human infections, especially in immune‐compromised patients. This is due to its unique ability to transform from a drug‐tolerant planktonic to a more dangerous and treatment‐resistant sessile life form, called biofilm. Recently, two derivatives of the frog skin antimicrobial peptide esculentin‐1a, i.e. Esc(1‐21) and its D‐amino acids containing diastereomer Esc(1‐21)‐1c, were characterized for their powerful anti‐Pseudomonal activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 92 publications
(120 reference statements)
0
42
0
1
Order By: Relevance
“…It was shown that various AMPs on their own not only eliminate planktonic bacteria, but also weaken the primary adhesion of bacterial cells to the surface, and within the established biofilms can impair the interaction of the elements of extracellular matrix and embedded bacterial cells. In addition, more specific mechanisms were revealed for a number of peptides demonstrating strong antibiofilm capabilities: they can modulate the motility of bacterial cells; affect the quorum sensing signaling; impede the work of the (p)ppGpp alarmone and, by extension, interfere with bacterial stringent response, and reduce the synthesis of various matrix elements or lead to their degradation (Pletzer and Hancock, 2016;Yasir et al, 2018;Casciaro et al, 2019;Shahrour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that various AMPs on their own not only eliminate planktonic bacteria, but also weaken the primary adhesion of bacterial cells to the surface, and within the established biofilms can impair the interaction of the elements of extracellular matrix and embedded bacterial cells. In addition, more specific mechanisms were revealed for a number of peptides demonstrating strong antibiofilm capabilities: they can modulate the motility of bacterial cells; affect the quorum sensing signaling; impede the work of the (p)ppGpp alarmone and, by extension, interfere with bacterial stringent response, and reduce the synthesis of various matrix elements or lead to their degradation (Pletzer and Hancock, 2016;Yasir et al, 2018;Casciaro et al, 2019;Shahrour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, for most AMPs, the bacterial membrane is the main target. Among the peptides investigated in the present study, the natural AMPs indolicidin [Selsted 1992;Falla 1996], LL-37 [Turner 1998, Barns 2013, novocidin [Gottlieb 2008, Nielsen 2010, the bee toxin melittin [Bucki 2004, Yang 2018 [Savini 2020, Casciaro 2019. For instance, indolicidin and LL-37 bind DNA (as many cationic AMPs do), but the role of this phenomenon in the mechanism of bacterial killing is debated [Marchand 2006, Ghosh 2014, Mardirossian 2014, Zhu 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm-modulating action of MIC and sub-MICs depends on many factors: type of antimicrobial, mode of action, bacterial strain and susceptibility or resistance of the strain. Moreover, a not-linear dose-dependent effect on biofilm modulation has been reported [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%